Dominant positive and negative selection using a hygromycin phosphotransferase-thymidine kinase fusion gene. - Lupton, S D (1991)
The hygromycin phosphotransferase gene was fused in-frame with the herpes simplex virus type 1 thymidine kinase gene. The resulting fusion gene (termed HyTK) confers hygromycin B resistance for dominant positive selection and ganciclovir sensitivity for negative selection and provides a means by which these selectable phenotypes may be expressed and regulated as a single genetic entity.